RESPONSE OF CALCAREOUS NANNOPLANKTON MORPHOLOGY TO ENVIRONMENTAL PERTURBATIONS: THE LATEST CENOMANIAN OCEANIC ANOXIC EVENT 2 AND LAB SIMULATIONS - G. Faucher (Università degli Studi di Milano, 2015)
Anthropogenic emissions of carbon dioxide into the atmosphere has indirectly driven acidification and reduced carbonate saturation of the oceans. Among calcareous plankton, coccolithophore algae are the major producers of pelagic CaCO3 in the modern ocean: they are direct contributors of the ocean biogeochemical cycles and climate system and, therefore, coccolithophore sensitivity to changes in surface water conditions is of major concern. Coccolithophores build around the cell an exoskeleton of calcite (coccosphere) that consists of single platelets called coccoliths and nannoliths. This phytoplanktonic group are affected by changes in surface water temperature, fertility, salinity, light and consequently are important instrument to A) predict the future state of the ocean, particularly its carbonate chemistry B) to reconstruct changes in past surface-water conditions. This PhD thesis is aimed to combine the geological and biological approaches, quantifying tempo and mode of coccolithophore response to specific combinations of stressing environmental conditions through investigation of a geological case history and laboratory experiments trying to simulate conditions of the past. During the Aptian Oceanic Anoxic Event 1a (OAE 1a) an extreme global perturbation of the atmosphere-ocean system was documented, with evidence of geologically rapid warming associated to ocean fertility and acidification at global scale. Erba et al. (2010) demonstrated that calcareous nannoplankton was extremely sensitive to ocean acidification during OAE 1a, allowing separation of most-, intermediate-, and least-tolerant taxa. After a major calcification failure of heavily calcified forms, ephemeral coccolith dwarfism and malformation represent the most remarkable species-specific adjustments to survive surface water acidity. The case history I focused on, is the latest Cenomanian Oceanic Anoxic Event 2 (OAE 2, ~ 94 Ma) which represents a profound perturbation of the ocean-atmosphere system caused by natural CO2 emissions related to ...